3D Translation

This is a straightforward extension of the 2D translation transformation:

                                (1  0  0  0) 
(x' y' z' 1)  =  (x  y  z  1) * (0  1  0  0)
                                (0  0  1  0)
                                (Tx Ty Tz 1)

which gives: x' = x + Tx
	     y' = y + Ty
	     z' = z + Tz

Note: to do an inverse Translation in 3D, replace Tx with -Tx, Ty with -Ty, and Tz with -Tz then T (T-1) = 1 (identity matrix)


From HyperGraph -- see details 26.11.1996